Evaluation of rapid immunochromatographic card test in comparison with IgM ELISA in diagnosis of dengue fever at a tertiary care hospital, South India - Tabassum, Samina Kausar; Ahmed, Syed Imran (International Journal of Research in Medical Sciences, 2022)
Background: Dengue has emerged as a major public health concern throughout India because of the mortality and morbidity associated with it. It is the most common mosquito-borne viral disease of humans. Hence early and rapid laboratory diagnosis of dengue is crucial. This study aims to determine demographic, clinical and laboratory investigations of all the suspected cases of dengue fever and comparison of two commercial tests routinely useful in diagnosis of dengue fever. This study was conducted to determine seropositivity of dengue samples in patients suspected of dengue illness and to compare immunochromatographic card test (ICT) test and IgM ELISA test. Methods: A total of 702 serum samples from patients with suspected dengue infection were included and the study was undertaken at department of microbiology at a tertiary care hospital, Hyderabad from July to December 2021. All samples were subjected to rapid ICT and confirmed by dengue IgM-capture ELISA. Results: Out of 702 cases suspected of dengue, 85 (12%) samples were positive by IgM ELISA method. The most affected age group was 21-40 years with 55 cases (64.3%) were positive, followed by the age group 0f 0-20 years with 25% of the cases. Males were affected more than females with a percentage of 54% and 46% respectively. The highest number of suspected dengue patients admitted was in the month of September, i.e., 140 with 16 positive (14.81%) followed by August 122 samples (12.16%) and October 110 samples with 14 (11.03%) positive. The sensitivity and specificity of ICT was 95.5% and 100% when compared with IgM-ELISA. Conclusions: Dengue cases were more during August to November in the monsoon and post monsoon season which is useful to plan special preventive strategies. This study draws attention toward the male, young and adult age group. To conclude, in countries lacking infrastructure for the diagnostic labs especially in the rural and remote areas, the rapid dengue ICT tests can play a major role in diagnosis and in patient management of acute dengue infection. The rapid ICTs are very simple, easy to perform, and can be used as point of care tests. We suggest that the rapid ICT for dengue detection may be used in patients presenting with febrile illness.